Cognitive And Affective Factor In Learning Proses (Faktor Kognitif dan Afektif dalam Proses Pembelajaran) - Mawardi, Anjali Fitrah; Pasiska, Pasiska; Ngimadudin, Ngimadudin (Edification Journal : Pendidikan Agama Islam, 2022)
This article will review the various meanings of learning. However, there are some understandings among them which state that demonstration learning contains changes in someone who has demonstrated learning. The development is intentional, positive and dynamic, and beneficial. The nature of intentionality implies that changes occur due to experiential practices that are applied by students intentionally or unintentionally, and not by chance. Positive treatment implies that the change is of equal value to the student's assumptions, and creates something new that is superior to the previous one. The dynamic nature implies that change occurs because of the efforts made by students, not without other people, for example because of the development cycle. The nature of success implies that the change has an impact and benefits for students. The practical nature implies that the change is durable enough and can be replicated or used at any point required. Learning changes can appear as abilities, tendencies, perspectives, gains, information, or appreciation.